Surrounded by art : panoramic views of America's landmark museums - Schiff, Thomas R. (Rizzoli Electa, 2019)
"In sweeping tableaux, photographer Thomas R. Schiff presents, America's most important art museums, using breathtaking photographs that compels us to revisit historic and modern cultural institutions and their storied rooms in a genuinely new light. Schiff skillfully combines his love of photography and architecture and profiles museums of all sizes and stripes across the country, showcasing the country's most stately institutions and newer cutting-edge buildings and building additions including Museums of Fine Arts, Boston; The Metropolitan Museum of Art, NY; Corcoran Gallery of Art, Washington, DC; Pennsylvania Academy of the Fine Arts, Philadelphia, PA; and Nelson-Atkins Museum, Kansas City, MO; among many others. Schiff's fresh, dynamic photographs are sure to appeal to architecture, museum, and art lovers alike."--Jacket flap.